2002
DOI: 10.1007/s00424-002-0858-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 72, a chaperone abundant in renal papilla, counteracts urea-mediated inhibition of enzymes

Abstract: Urea, at concentrations routinely observed in the renal inner medulla during antidiuresis in many mammals, is a potent protein destabilizing agent that reduces the activity of many enzymes. The molecular chaperone heat shock protein 72 (HSP72) is expressed at about 5 ng/ micro g protein in the renal papilla and is thus 40 times more abundant than in the isosmotic cortex and may counteract the deleterious effects of high urea concentrations in the inner medulla. To test this hypothesis, we examined the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…11). These data are in agreement with previous investigations in which over-expression of HSP70 robustly increased the resistance of MDCK cells against high urea concentrations [7], a phenomenon which is mediated at least in part by the chaperoning effects of HSP70 on cellular enzymes at high and protein-destabilizing urea concentrations [8]. Another example of HSP70-mediated cell protection relevant to the kidney was presented by Bidmon et al [35].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…11). These data are in agreement with previous investigations in which over-expression of HSP70 robustly increased the resistance of MDCK cells against high urea concentrations [7], a phenomenon which is mediated at least in part by the chaperoning effects of HSP70 on cellular enzymes at high and protein-destabilizing urea concentrations [8]. Another example of HSP70-mediated cell protection relevant to the kidney was presented by Bidmon et al [35].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, urea enters the cells rapidly and thus constitutes no major osmotic stress. Urea, however, at concentrations routinely observed in the renal inner medulla during antidiuresis, is a potent protein-destabilizing agent which reduces the activity of various enzymes and induces apoptosis in cells that are not adequately protected [6][7][8]. Interestingly, heat shock protein 70 (HSP70), a chaperone abundantly expressed in the renal papilla, confers resistance against the adverse effects of high urea concentrations to renal medullary cells and counteracts ureamediated inhibition of enzymes [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This counteraction of urea effects by Hsp70 can be due to its chaperonic activity as Hsp70 has been found to increase the urea-induced decreased activity of several enzymes (Neuhofer and Beck, 2005). Besides this, HSP like Hsp72 has also been found to attenuate the urea-induced activity decrease of beta-galactosidase and lactate dehydrogenase (Neuhofer et al, 2002). Hsp72 and 70, have been found to confer protection against urea induced apoptosis (Colmont et al, 2001;Santos et al, 1998b;Zhang et al, 2000) probably by the suppression of c-Jun amino-terminal kinase, enzyme normally activated in apoptosis, by Hsp72 (Gabai et al, 2000;Yaglom et al, 1999) and inhibition of release of cytochrome c and Apaf-1 from mitochondria by Hsp70, thus preventing the implementation of apoptotic pathway (Beere et al, 2000).…”
Section: Counteraction Of Urea At Cellular Levelmentioning
confidence: 93%
“…These urea protective effects on NaCl induced apoptotic effects were also found to be dose dependent also. In another development, several studies revealed that this counteraction of urea effects by NaCl has been found to be due to the presence of heat shock proteins like Hsp27, Hsp70 and Hsp72 under in vivo conditions (Neuhofer et al, 2002). Interestingly, synthesis of heat shock proteins like small Hsp27, Hsp70, Hsp72 and osmotic stress protein 94/Hsp110 was found to be up-regulated in different types of cells including papillary collecting duct, papillary interstitial, MDCK and IMCD cells.…”
Section: Counteraction Of Urea At Cellular Levelmentioning
confidence: 96%